Analisis Dan Perancangan Sistem Pakar Untuk Mendiagnosa Penyakit Vertigo Dengan Metode Dempster Shafer - Sihombing, Arfyantina; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2021)
To diagnose vertigo, knowledge of a disease specialist is needed, namely a Neurologist. Most people are still often difficult to directly see a specialist doctor and how to choose the right course of action for people with vertigo. The developed system is an expert system to diagnose vertigo using the Dempster Shafer method, which is to find the diagnosis of vertigo. Expert systems are computer-based systems that use knowledge, facts, and reasoning techniques in solving problems that can usually only be solved by an expert in that field. Diagnosis is done by analyzing the input of symptoms in the form of a choice of symptoms in accordance with what is experienced by the patient. Each symptom has been given a value obtained from an expert who then input the selected symptoms are processed and calculated using the Dempster Shafer formula.